136k views
3 votes
Find an explicit rule for the nth term of the sequence.

-4, -8, -16, -32, ...

A.) an = -4 • 2n - 1
B.) an = 2 • -4n + 1
C.) an = 2 • -4n
D.) an = -4 • 2n

User GILGAMESH
by
5.2k points

1 Answer

5 votes

Find the difference between the existing terms:

-8 / -4 = 2

-16/-8 = 2

This means the next term is the previous term multiplied by 2:

The first term is given as -4

You would start with the first term ( -4) then multiply it by the difference of terms ( 2) raised to the nth term (n) minus 1.

An = -4 * 2^n-1

The answer is A

User DrDavid
by
5.4k points